Combined Detection of NUDT15 Variants Could Highly Predict Thiopurine-induced Leukopenia in Chinese Patients with Inflammatory Bowel Disease: A Multicenter Analysis. Issue 9 (24th May 2017) - Chao, Kang; Wang, Xueding; Cao, Qian; Qian, Jiaming; Wu, Kaichun; Zhu, Xia; Yang, Hong; Liang, Jie; Lin, Lang; Huang, Zicheng; Zhang, Yu; Huang, Yibiao; et al.
Abstract : Background: NUDT15 c.415C>T was a novel genetic marker confirmed in our center for thiopurine-induced leukopenia in Chinese inflammatory bowel disease (IBD). For validation, a large cohort study is needed. Meanwhile, the newly discovered NUDT15 coding variants (c.36_37insGGAGTC and c.52 G>A) have not been studied in patients with IBD. We aimed to further confirm the influence of 3 NUDT15 variants (c.415C>T, c.36_37insGGAGTC, and c.52G>A) on thiopurine-induced leukopenia in Chinese patients with IBD. Methods: Patients prescribed on thiopurines for at least 2 weeks were recruited from 4 tertiary hospitals. Clinical data were collected. NUDT15 genotypes were determined with polymerase chain reaction-RFLP and sequencing. The interactions between variants and leukopenia were analyzed. Results: A total of 732 patients were included, 177 (24.3%) of whom developed leukopenia. There were strong associations of NUDT15 c.415C>T, c.36_37insGGAGTC, and c.52G>A with thiopurine-induced leukopenia ( P = 1.81 × 10 −20, P = 4.74 × 10 −8 and P = 0.04, respectively), whereas there was no relevance for thiopurine S-methyltransferase genotypes ( P = 0.25). The predictive sensitivity of NUDT15 c.415C>T was 49.2%, whereas it increased to 55.4% when combined analysis with c.36_37insGGAGTC and c.52G>A. Notably, not only the homozygotes with NUDT15 c.415C>T but also the heterozygotes both carrying c.415C>T and c.52G>A developed early leukopenia. The median dosage for NUDT15 c.415C>T carriers was significantly lower than that for wild-type ( P < 0.001). Conclusions: We confirmed that NUDT15 c.415C>T, c.36_37insGGAGTC, and c.52G>A variants were risk factors for thiopurine-induced leukopenia. Combined detection of the 3 variants could increase the predictive sensitivity of thiopurine-induced leukopenia and help to distinguish early leukopenia in heterozygote of c.415C>T in Chinese patients with IBD. Treatment monitoring by NUDT15 variants may be promising in individualized therapy.